ILLOCUTIONARY ACTS IN ELLEN DEGENERES TALK SHOW - Gelora S. Girsang; Amrin Saragih (LINGUISTICA, 2014)
ABSTRACT   This study deals with the types of illocutionary acts in Ellen Degeneres Talk show. The objectives of this study were to describe the types of illocutionary Acts which were used in Ellen Degeneres Talk show, to discover the type of illocutionary act which was dominantly used in Ellen Degeneres Talk show, why it is dominant and to elaborate in what contexts the dominant type occurs. This research applied descriptive qualitative method. It took two episodes of Ellen Degeneres Talk Showwhich is taken randomly from internet. Based on the analysis, not all types of illocutionary acts were used in Ellen Degeneres Talkbecause Declarative is not found.There were 326 utterances in two episodes selected, and the percentages of data were 43.86% ofassertives, 30.67% of directives, 18.40% of expressives, 6.13% of commisives and 0% of declaratives. The writer does not find declarations in the dialogue because there is no utterance that has a function that can change the world or the status of people through speaker’s utterance. The most dominant type of illocutionary acts found was Assertives. It shows that in their conversation the host most gave information and statement because it happened in the context of talk show where Ellen as the host gave some information about her guess star, information about the theme of the show and also about guest’s personal life and career.   Keywords:Pragmatics, Speech Acts, Illocutionary Acts